Physics mechanics and chemical evaluation on walls used after fire (Gaceta Técnica, 2015)
This research is intended to evaluate the behavior of lightened concrete blocks and expanded high density polystyrene when exposed to heat, that are used in slabs and enclosures in prototype buildings. It is part of a field research, experimental and analytical-descriptive, for which six phases were carried out: collection of information, physical-mechanical character of coating to use, prototypes or modules to be tested, description of the scheme of testing, physical-chemical character of the materials under study and development of safety recommendations in case of fire characterization. The necessary information on expanded polystyrene high density, and lightweight blocks with expanded clay was collected through consultation of texts, manuals, standards, colleges, shops, online publications, trained personnel with experience using these materials. The specialized company International Fire Services C.A. (IFSCA) conducted the study required under standards. Among the key findings there were the high levels of volatile organic compounds during combustion of expanded polystyrene and characteristics of the lightweight expanded clay blocks as thermal insulators were found
Keywords: concrete lightweight; expanded polystyrene; toxic gases